АМБИВАЛЕНТНОСТА НА МОТИВОТ НА ЗМИЈАТА (Philological Studies, 2019)
This article deals with the semantic study of the motif of the serpent in various myths, folk beliefs, rituals, dreams, as well as literary achievements; in effect, with the goal to promote through practice a variety of different views and ambivalent interpretations. Its presence is seen as early as that of archaic societies, whence it had a significant mythical and religious meaning. What is particularly important in said context is that it is truly experienced in the rituals, through which, according to M. Eliade, it purports to explain some puzzling questions about human existence, among other things, how man was created, how to protect from evil, and how to continue our species. Today, many prominent ethnologists, anthropologists, mythologists, and psychologists endeavor to discover, from different angles, the semantics and meaning of the archetype of the serpent. Their attempts have proven that the serpent occupies one of the leading positions when it comes to the interpretation of the two basic principles of humanity (a spirit of creation and of cognition). Although in terms of everyday life, the serpent is seen as a relic of the past, as a "sacred story" that lost its meaning, or even as a stage that has been overcome in the development of human thought; scientists and culturologists, however, treat this motif with special interest. They attach great importance to it mainly because of its visible presence in literature and other modern forms of spiritual achievement. This certainly speaksto the invaluable importance of this motif in the effort to understand man as a whole.
Keywords: motif of the serpent, archetype, semantics, ambivalent interpretations, myths, folk beliefs, rituals, dreams, literary achievements